Mental health comorbidity in patients with atopic dermatitis - Yaghmaie, Pouya; Koudelka, Caroline W.; Simpson, Eric L. (Journal of allergy and clinical immunology, 2013)
Recent data, primarily from Europe, suggest that children with atopic dermatitis (AD) might be at increased risk of mental health disorders. We aimed to quantify the mental health burden associated with pediatric AD in the United States. A cross-sectional study design was used analyzing data from the 2007 National Survey of Children's Health, a survey reporting on the health status of 92,642 noninstitutionalized children aged 0 to 17 years. The lifetime prevalence of various provider-diagnosed mental health conditions was calculated for those with and without a history of AD. The odds of having attention deficit hyperactivity disorder was significantly increased in children with AD compared with the odds in control subjects without AD (odds ratio, 1.87; 95% CI, 1.54-2.27), even after controlling for known confounders. The adjusted odds ratios for depression, anxiety, conduct disorder, and autism were 1.81 (95% CI, 1.33-2.46), 1.77 (95% CI, 1.36-2.29), 1.87 (95% CI, 1.46-2.39), and 3.04 (95% CI, 2.13-4.34), respectively, and these estimates were all statistically significant. A clear dose-dependent relationship was observed between the prevalence of a mental health disorder and the reported severity of the skin disease. Our data reveal a striking association between mental health disorders and AD in the US pediatric population. The severity of the skin disease alters the strength of the association. Prospective cohort studies are needed to verify these associations and to explore underlying mechanisms. Strategies to prevent AD or to aggressively treat early skin inflammation might modify the risk of mental health disorders in at-risk children.